2005
DOI: 10.1145/1080695.1069971
|View full text |Cite
|
Sign up to set email alerts
|

Architecture for Protecting Critical Secrets in Microprocessors

Abstract: We propose "secret-protected (SP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 18 publications
0
26
0
3
Order By: Relevance
“…Partitioning: Many secure caches partition the cache lines (tag and data) between the victim and the attacker [23]- [26], [47], but the replacement policy and state is not considered and specified. For example, in Partition-Locked (PL) cache [24], each cache line is extended with one lock bit.…”
Section: B Lru Attack and Secure Cachesmentioning
confidence: 99%
“…Partitioning: Many secure caches partition the cache lines (tag and data) between the victim and the attacker [23]- [26], [47], but the replacement policy and state is not considered and specified. For example, in Partition-Locked (PL) cache [24], each cache line is extended with one lock bit.…”
Section: B Lru Attack and Secure Cachesmentioning
confidence: 99%
“…There are a number of other works that provide isolated environments for trusted software modules [Lie et al 2000;Suh et al 2003;Lee et al 2005;Dwoskin and Lee 2007;McKeen et al 2013;Anati et al 2013;Hoekstra et al 2013;Boivie 2012;Owusu et al 2013;Evtyushkin et al 2014]. Haven [Baumann et al 2014] demonstrated a system to achieve protected execution on unmodified binaries using SGX hardware support [McKeen et al 2013].…”
Section: Hardware-supported Approachesmentioning
confidence: 99%
“…Architectural support for VM security. There have been architectural solutions to protecting applications and data from powerful software attacks [43,44]. Recent efforts [45,46] try to address this issue by means of architectural support.…”
Section: Related Workmentioning
confidence: 99%